Pengaruh Operasi Katarak Terhadap Ketajaman Visual - Raymond Tanjung (Publikasi Indonesia, 2022)
The quantity of cataract surgery has long been an important public health indicator to assess health accessibility. Standards for cataract surgery are developing around the world. The cataract surgery revolution never stops and continues, from intracapsular cataract extraction, and extracapsular cataract extraction, to phacoemulsification. In developed countries, phacoemulsification is the main method of cataract surgery. The overall visual acuity outcome after cataract surgery is considered very good and effective in the long term. However, several factors such as refractive errors, ocular comorbidities, and surgical complications still significantly reduce satisfaction with cataract surgery results, especially in developing countries. In addition, sociodemographic factors such as socioeconomic status and education level were also identified as lowering postoperative vision quality scores. To determine the effect of cataract surgery on visual acuity. The method used in writing this article is a literature review. Results: Cataract surgery is a relatively safe and effective procedure. Most (84% to 94%) eyes achieved the best visual acuity correction, achieving 20/30 (6/9) or better about six months after surgery. The results of visual improvement from cataract surgery with intraocular lens implantation are generally very satisfactory. But the results are less than satisfactory in low-income countries.